Effect of Sucrose on the Rheology and 3D Printability of Pregelatinized Rice Flour Paste - Dongju Lee; Mohammed I. Saleh; Youngseung Lee (Foods)
Although sucrose plays a crucial role in influencing the rheological and textural properties of sucrose–starch-based blends, its effects on the 3D printability and rheological behavior of α-rice flour paste remain largely unexplored. This study aimed to investigate the impact of varying sucrose concentrations (0, 1, 2, 3, and 4% w/w) on the printability and rheological properties of α-rice flour paste. Printability was evaluated using a 3D food printer, while rheological properties were analyzed using a rheometer. All the samples exhibited shear-thinning behavior. As the sucrose concentration increased, both the maximum storage modulus (G′Max) and yield stress (τy) decreased significantly, while the printing percentage error and deformation factor increased. A strong negative linear correlation was observed between G′Max, τy, and the printing percentage error (R2 = 0.94, 0.95), whereas the deformation factor exhibited a negative quadratic correlation (R2 = 0.99, 0.94). These results indicate that a decrease in α-rice flour concentration combined with sucrose addition weakens viscoelastic properties, resulting in lower structural stability and greater deformation. This study confirms the role of α-rice flour in enhancing starch’s physical and functional properties and provides fundamental data for optimizing 3D printing with α-rice flour–sucrose paste.